Challenges of Coming Out: Inputs in Improving Mental Health - Maniago, Jestoni D. (European Scientific Journal, ESJ, 2018)
Homosexuals face challenges in unraveling their personality, thus, the process of coming- out becomes a very difficult experience. Most of the homosexuals are craving for the liberty to express their personalities which they believe would give essence to their existence. They are hampered by various factors in the society in which they need to come across and gain acceptance and respect. This queer study reports on the process and findings of a mini- ethnography conducted in a gay organization in the Philippines. The aims of the study were to acquire a comprehensive understanding on the challenges encountered by the homosexual gay members during the process of coming out and to identify structural and cultural enablers or barriers in revealing their homosexual personality. Four themes were strongly identified: â€œinternalized homophobiaâ€, â€œperceived rejectionâ€, â€œpresence of homosexual friendsâ€ and â€œstrong desireâ€. These themes were seen to influence the homosexualâ€™s coming out process. If the culture of orientation disables gay homosexuals to come out, they would find a culture or make their own culture that would be worthy of their homosexual personality, giving them the liberty of life and security